A systematic review of studies measuring and reporting hearing aid usage in older adults since 1999: a descriptive summary of measurement tools - Perez, Elvira; Edmonds, Barrie A. (Public Library of Science, 2012)
Objective: A systematic review was conducted to identify and quality assess how studies published since 1999 have measured and reported the usage of hearing aids in older adults. The relationship between usage and other dimensions of hearing aid outcome, age and hearing loss are summarised.